HUBUNGAN HIPERTENSI DENGAN GANGGUAN FUNGSI KOGNITIF PADA LANSIA DI KLINIK RAWAT INAP MARDI WALUYO KOTAGAJAH - Nadya Lestari; Aulia Rahman (Jurnal JKFT, 2023)
The prevalence of hypertension in the Lampung area which includes cases and consuming hypertension drugs is around 8.7% (Riskesdas, 2018). in the Mardi Waluyo Inpatient Clinic, Kotagajah, hypertension cases until March 2021 reached 366 patients came to the first ranked  of the 10 largest non-infectious diseases. One of the complications of hypertension in the central nervous system other than stroke can also cause a decrease of the cognitive function. The purpose of this study was to determine the relationship between hypertension and cognitive function disorders in the elderly at Clinic of Mardi Waluyo, Kotagajah.This type of research is a quantitative research, using a cross sectional design. The population used in this study were all the elderly who suffer of the hypertension at the Mardi Waluyo Inpatient Clinic Kotagajah.This researh are used total sampling.The sample in this research are 37 peoples. Data collection using the chi square.The results showed that 17 respondents (45.9%)suffer the first grade of hipertension. Based on cognitive function, there were 21 respondents (56.8%)sustain the cognitive fungtion disorders. There is a relationship between hypertension and  cognitive function disorders on the elderly at the Mardi Waluyo Inpatient Clinic, Kotagajah (p value 0.041). It is recommended for the health workers are expected to be able to provide more information about hypertension and cognitive function disorders to the public.